Administrators’ views on supporting newly arrived students in Finland - Alisaari, Jenni; Harju-Autti, Raisa; Kaukko, Mervi; Heikkola, Leena Maria; Mustonen, Sanna; Petäjäniemi, Maria (Apples - Journal of Applied Language Studies, 2026)
This study examines Finnish municipal-level administrators’ (N = 4) insights on organizing and administering education for newly arrived students. The data were gathered through interviews and analyzed using thematic content analysis. All the municipalities where the participants worked had good practices for preparatory education for newly arrived students. However, variations in these practices indicate that more coherent national guidelines are needed. Post-preparatory education practices were less developed. Overall, there are some effective practices related to organizing and administering education for newly arrived students in Finland, which could be implemented internationally; however, further practices need to be developed to promote educational and social justice for all students.